2018
DOI: 10.1590/0034-7167-2017-0546
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and salivary cortisol in preterm neonates: a clinical, randomized, controlled, crossover study

Abstract: Ear protectors in preterm neonates did not influence the salivary cortisol level and total sleep time in the studied periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Serum cortisol is highly correlated with salivary cortisol measured in preterm infants [ 18 ]; however, there are few studies in the literature examining stress regulation in preterm infants measured by salivary cortisol levels that address the kangaroo method. Salivary cortisol has the limitation of having to require a sufficient amount of saliva for analysis due to the peculiar hyposalivation of preterm infants [ 19 ] despite the use of a stimulant [ 20 ]. Some studies have focused on maternal separation, examining stress and neuroendocrine responses to separation [ 21 ], but only a few studies have focused on early separation of preterm infants and the importance of maternal contact in the first few days and weeks of life [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Serum cortisol is highly correlated with salivary cortisol measured in preterm infants [ 18 ]; however, there are few studies in the literature examining stress regulation in preterm infants measured by salivary cortisol levels that address the kangaroo method. Salivary cortisol has the limitation of having to require a sufficient amount of saliva for analysis due to the peculiar hyposalivation of preterm infants [ 19 ] despite the use of a stimulant [ 20 ]. Some studies have focused on maternal separation, examining stress and neuroendocrine responses to separation [ 21 ], but only a few studies have focused on early separation of preterm infants and the importance of maternal contact in the first few days and weeks of life [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies involving cortisol often investigate diseases due to deficiency or excess secretion of this hormone in order to assess the physiological response to any stressful event (16)(17) . However, searches in the literature have shown that research on the subject with nurses from oncology sectors is still scarce, especially in Brazil, and mostly carried out with hospitalized patients in different hospital units (18)(19)(20) .…”
Section: Introductionmentioning
confidence: 99%